Legal protection for consumers (A juridical analysis of cosmetic products without halal label) - Elvira Fitriyani Pakpahan; Roy Saputra Manalu; Kerisna Sukma Adji Sembiring; Rona Indara; M.S. Alfarisi (Privietlab, 2023)
Along with the advancement of science, human needs have grown and are not limited to food and clothing. Self-care and appearance have also become important, not only for women but also for men. Many people use skin care products to keep their skin looking brighter and healthier. Caring for and beautifying yourself has become a trend. These products are easy to find and provide instant results at affordable prices. However, the Food and Drug Supervisory Agency (BPOM) warns that some cosmetics contain dangerous ingredients if used without a doctor's recommendation. Unscrupulous law enforcement and small fines make economic actors reluctant and afraid to distribute illegal cosmetics due to weak sanctions. The Consumer Protection Act number 8 of 1999 provides legal protection for consumers who experience losses and has a positive effect on the business world by taking action against business actors who break the law and harm society. This is expected to reduce risks for Indonesian consumers from fraudulent acts.